INFORMATION SUPPORT OF HYDRODRIVES LIFECYCLE - A. V. Puzanov (Informatika)
The paper discusses the ways of increasing the efficiency of production of hydraulic drives by using the information support of product life cycle. The article describes examples of the use of software systems for analyzes at different stages of the life cycle of hydraulic drives.